Visual Representation of Tv Commercials - Agung Farid Agustian; Nurul Syamsiah; Zahra Zahira; Rifpan Putra Afriansyah (Talenta Publisher, 2023)
The study focuses on visual meaning in commercial videos advertisement. The qualitative method is used as the research method in this research with a multimodal discourse analysis approach. Ideational meanings represent the commercial video's visual meaning. It was realized through participants, processes, and circumstances about differences, the easiness of life, and staying strong in difficult times. The representational meanings of the commercial videos were realized through the conceptual process. It symbolically represented the people's differences and needs. Visual representation implies how the product is a better choice for its customers. While in the end, the narrative process depicts actors and their environment as their goal to create representational meaning from the visual elements.